The influence of working capital on the profitability of food and beverage sector companies listed on the Indonesian stock exchange - Donita Nawangayu Ningsih; Handri, Handri (Jurnal Ekonomi, 2024)
The processing industry sector, represented by the food and beverage subsector, is the driving sector of the Indonesian economy. Competition in Indonesia's food and beverage sector shows consistent performance, involving both small and large companies that dominate market activity and maintain a high sustainability index. This research aims to analyze how much-working capital influences profitability with a high sustainability index in 2022. The working capital variable is the difference between the company's current assets and liabilities. In contrast, the profitability variable is calculated through the ratio of net profit to sales the company obtains. From the population of 18 food and beverage companies with a high sustainability index on the Indonesia Stock Exchange, a sample of 3 consistently performing companies was obtained for the study period. The sample selection technique employed was purposive sampling. Following data testing and selecting the preferred model, the data received will be subjected to panel data regression. The results of this research analysis provide empirical evidence that the working capital policies implemented by companies can significantly influence the profitability (ROA, ROE, EAT, and GOP) of companies in the food and beverage sector. The research substantially contributes to food and beverage industry companies by optimizing liquidity and managing working capital to improve profitability. These results can also serve as guidance for upcoming researchers investigating the factors that influence the financial performance of companies in the food and beverage sector to enhance overall profitability.